ECONOMIC LOSSES RESULTING FROM THE IMPACT OF ENVIRONMENTAL PROBLEMS ON THE AGRICULTURE OF UZBEKISTAN. SUITABLE METHODS FOR UZBEKISTAN USED BY DEVELOPED COUNTRIES TO OVERCOME INSTABILITY IN AGRICULTURE (Conferencea, 2022)
The objective of this article is to focus on current environmental problems, which are harmful for Uzbekistan’s agriculture and future economy, discussion on   methods of developed countries to address environmental problems and prevent agricultural system from instability.